Modified traditional water-harvesting system for irrigation - Ranade, D. H.; Mujalde, Santosh; Swarup, Indu (Indian Farming, 2019)
During Monsoon average rainfall in Malwa region of Madhya Pradesh is 1,000 mm. The high intense rains coupled with low infiltration rate of black soils of the region produces 22 to 25% runoff (220 to 250 mm) mainly from the cultivated fields despite all efforts to restrict runoff using various soil and water conservation measures viz. use of mechanical or vegetative barriers within the fields, sowing across the slope and planting of more surface area covering crops like soybean during kharif. The major constraint in growing a second crop in many areas particularly in Malwa region is the lack of suitable irrigation water. Therefore, creating water storage tanks in the cultivated field for storing the excess runoff (common feature in this region due to low infiltration rate of the soil and high intense rainfall) is one of the best options available with the farmers.